Brochure promoting Hitt's Fireworks - Richard Nicol
Located in Rainier Valley, Hitt Fireworks was a world renowned fireworks manufacturer. They did displays for the 1909 Alaska-Yukon-Pacific Exposition, the Queen of England and the 4th of July celebrations into the 1970's. Hitt Fireworks also did special effects for movies such as ""Gone With the Wind"".